ANALISIS EFISIENSI TATANIAGA SAYURAN DAUN DI PASAR TRADISIONAL - Riadhotul huda, Wafi; Miftah, Himmatul; Yoesdiarti, Arti (JURNAL AGRIBISAINS, 2021)
Vegetables can be in the form of plants or parts of plants that are consumed fresh or ripe as part of the diet. There are very diverse types of vegetables in the form of tubers, fruit, flowers or leaves. Leaf vegetables are the type most consumed. 97.29% of the Indonesian population consumes vegetables, the types of vegetables consumed by the Indonesian population are leaf vegetables such as kale, chicory and caisim. The purpose of this research is to analyze the efficiency of trading channels and marketing functions carried out by each marketing actor in the Bogor City Traditional Market by using trading margin, farmer share, profit ratio and R / C cost. This research was conducted on the trading channel actors in the Traditional Market in Bogor City. The number of respondents in the study were 15 farmer respondents and 42 merchant respondents from both markets. The data analysis used purposive method for lapak traders and snowball sampling from retailers to farmers. The results of this study were four leaf vegetable trading channels in the Traditional Market of Bogor City with the efficiency level of the three vegetables considered to be the most efficient, namely channel IV on kale vegetables, channel II on chicory and channel IV on caisim, with each having a margin of yield of 3500, 800, 700 and the highest farmer's share was 82.93%, 81.40% and 59.52%. Thus it is necessary to do more analysis related to the strategy of developing vegetable commodities of kale, chicory and caisim in traditional markets related to marketing activities.